Analisis Pengembangan Literasi Peserta Didik Melalui Kegiatan Pojok Baca - Itsna Septiani Wicaksono; Aang Fitro Hidayat; Bagas Satria Badalu; Shabrina Diva Alfania; Rajib Hayyi Jenesha (Forum Kerjasama Pendidikan Tinggi, 2024)
Overall, the Industrial Revolution 4.0 brings new challenges and opportunities for education. In order to prepare young people for an increasingly digital and connected future, the education system must continue to innovate, update the curriculum, and ensure that all levels of society can access relevant and quality education in this era. reading corner activities that are attractively designed and provide various types of books can increase students' interest in reading. From the results of observations obtained by researchers in several elementary schools during the real work lecture program, especially at SDN Singopadu, Tulangan, Sidoarjo, a problem was found, namely the low reading literacy caused by the lack of reading facilities at the school, so this problem became the benchmark for researchers in the problem. The success of the reading corner in schools can be seen from the perspective of teachers and students. Based on the focus of this research problem, the research approach at Singopadu State Elementary School used descriptive qualitative research methods. The type of research used in this study is a case study. From the teacher's perspective, the reading corner not only functions as a place to read, but also as a means to support the teaching and learning process. Meanwhile, from the perspective, the existence of the reading corner provides a positive experience that makes them more interested in reading. Thus, with the support of all school parties, especially the support of teachers and the active participation of students, the reading corner can continue to grow and provide greater benefits to the school community of SDN Singopadu.